2015
DOI: 10.1007/7651_2015_257
|View full text |Cite
|
Sign up to set email alerts
|

Directed Myogenic Differentiation of Human Induced Pluripotent Stem Cells

Abstract: Patient-derived induced pluripotent stem cells (iPSCs) have opened the door to recreating pathological conditions in vitro using differentiation into diseased cells corresponding to each target tissue. Yet for muscular diseases, a method for reproducible and efficient myogenic differentiation from human iPSCs is required for in vitro modeling. Here, we introduce a myogenic differentiation protocol mediated by inducible transcription factor expression that reproducibly and efficiently drives human iPSCs into my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…MyoD overexpression was found to inhibit Twist-1 through miR-206 induction, resulting in an increase in muscle cell differentiation (Koutalianos et al, 2015). Overexpression of MyoD1, using a vector to human-induced pluripotent stem cells, promotes these cells to undergo myogenic differentiation (Shoji et al, 2015). The overexpression of TAZ, which is known as a modulator of osteogenic and adipogenic differentiation of MSCs, was found to increase MyoD-mediated myogenic differentiation.…”
Section: Myogenic Differentiationmentioning
confidence: 99%
“…MyoD overexpression was found to inhibit Twist-1 through miR-206 induction, resulting in an increase in muscle cell differentiation (Koutalianos et al, 2015). Overexpression of MyoD1, using a vector to human-induced pluripotent stem cells, promotes these cells to undergo myogenic differentiation (Shoji et al, 2015). The overexpression of TAZ, which is known as a modulator of osteogenic and adipogenic differentiation of MSCs, was found to increase MyoD-mediated myogenic differentiation.…”
Section: Myogenic Differentiationmentioning
confidence: 99%
“…Transduced iPSCs represent a stable and expandable population, in which doxycycline treatment and medium switch are sufficient to induce myogenic differentiation in few days. Even if we do not provide comparative analysis, a survey in the literature suggests similar timing and efficiency of differentiation with our system compared to analogous methods (Tanaka et al, 2013, Shoji et al, 2016). …”
Section: Discussionmentioning
confidence: 93%
“…It has been previously shown that inducible expression of a MyoD transgene carried by a piggyBac vector could induce iPSC muscle differentiation (Tanaka et al, 2013, Shoji et al, 2016). The enhanced version of piggyBac (epB) carries an engineered terminal repeat, which increases transposition efficiency in human pluripotent stem cells (Lacoste et al, 2009, Rosa and Brivanlou, 2011, Rosa et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Myogenic induction of ESCs and iPSCs has also been shown by inducing expression of Met Activating Genetically Improved Chimeric Factor-1 [112]. The myogenic regulatory factor Myo-D has also proved to be useful for the induction of myogenesis in iPSCs [113]. Here, transplantation of the differentiated cells ameliorated the dystrophic phenotype, restored depleted progenitors and improved functional capacity of the muscle.…”
Section: Myogenesis Via Genetic Manipulationmentioning
confidence: 99%